Comparison of the Efficacy of Surgical Decompression Alone and Combined With Canine Adipose Tissue-Derived Stem Cell Transplantation in Dogs With Acute Thoracolumbar Disk Disease and Spinal Cord Injury - Bach, Fernando Swiech; Rebelatto, Carmen Lucia Kuniyoshi; Fracaro, Leticia; Senegaglia, Alexandra Cristina; Fragoso, Felipe Yukio Ishikawa; Daga, Debora Regina; Brofman, Paulo Roberto Slud; Pimpão, Claudia Turra; Engracia Filho, Jair Rodini; Montiani-Ferreira, Fabiano; Villanova, José Ademar (Frontiers in Veterinary Science, 2019)
Paraparesis and paraplegia are common in dogs. The most common cause of these conditions is herniated disc disease in the thoracolumbar segment (T3-L3), which is a neurological emergency. Surgical decompression should be performed as soon as possible when spinal compression is revealed by myelography, computed tomography, or magnetic resonance imaging. Mesenchymal stem cell therapy is a promising alternative for treating spinal cord injury. This study sought to evaluate the effects of surgical decompression and allogeneic transplantation of canine adipose tissue-derived mesenchymal stem cells (cAd-MSCs) on acute paraplegia in dogs. Twenty-two adult dogs of different breeds, which had acute paraplegia resulting from Hansen type I disc herniation in the thoracolumbar region (T3-L3), were evaluated using computed tomography. All of the dogs presented with grade IV or V lesions and underwent surgery within seven days after the onset of clinical signs. The patients were randomly divided into two groups containing 11 dogs each. The Group I dogs underwent hemilaminectomy, and the Group II dogs underwent hemilaminectomy and cAd-MSC epidural transplantation. In both groups, all of the dogs with grade IV lesions recovered locomotion. The median locomotor recovery period was seven days for Group II and 21 days for Group I, and this difference was statistically significant (p < 0.05). Moreover, the median length of hospitalization after surgical decompression was statistically different between the two groups (Group I, four days; Group II, three days; p < 0.05). There were no statistically significant group differences regarding the number of animals with grade IV or V lesions that recovered locomotion and nociception. In conclusion, compared with using surgical decompression alone, the use of epidural cAd-MSC transplantation with surgical decompression may contribute to motor improvement in dogs with acute paraplegia by reducing the length of post-surgery hospitalization as well as the time to locomotor recovery.